2021
DOI: 10.1111/ppl.13480
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals the inhibitory nature of high nitrate during adventitious roots formation in the apple rootstock

Abstract: In the process of vegetative propagation of apple rootstocks, the development of adventitious roots (ARs) has crucial importance. Nitrate is an essential nutrient necessary for plant growth; however, the inhibitory effect of high nitrate on ARs formation has not been explored. The physiological and molecular mechanisms underlying ARs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Furthermore, JA has been identified as a suppressive factor for the formation of ARs in Arabidopsis that acts downstream of the auxin pathway [39]. Comparable findings were also reported in apples, where increased JA accumulation at the stem basal sections of the apple rootstock prevents AR formation [17,20]. The concentration of JA-me and the expression of related genes were considerably higher in PEG-treated cuttings, showing that increased JA-me accumulation is detrimental for AR formation in GL-3 apple cuttings (Figures 5A,B and 7 and Table S6).…”
Section: The Role Of Hormonal Contents and Related Degs In Peg-induce...mentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, JA has been identified as a suppressive factor for the formation of ARs in Arabidopsis that acts downstream of the auxin pathway [39]. Comparable findings were also reported in apples, where increased JA accumulation at the stem basal sections of the apple rootstock prevents AR formation [17,20]. The concentration of JA-me and the expression of related genes were considerably higher in PEG-treated cuttings, showing that increased JA-me accumulation is detrimental for AR formation in GL-3 apple cuttings (Figures 5A,B and 7 and Table S6).…”
Section: The Role Of Hormonal Contents and Related Degs In Peg-induce...mentioning
confidence: 76%
“…ABA is a stress-responsive hormone that is required for plant dormancy and stress tolerance. Several studies have revealed that ABA has a negative effect on root formation and development [17,18]. Compared with CK cuttings, PEG-treated cuttings hold significantly higher ABA content at all time points during the formation of ARs (Figure 5A).…”
Section: The Role Of Hormonal Contents and Related Degs In Peg-induce...mentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, studies have targeted apple tissues to explore global N tolerance using RNA-seq analysis [22,23]; however, the detailed metabolic signals associated with N stress responses have not been investigated well. Our transcriptome data of apple leaves collected under contrasting N stress conditions provided valuable information about the expression dynamics of genes associated with each N-deficient/excessive stress response.…”
Section: Discussionmentioning
confidence: 99%
“…In apple orchards, proper N fertilization is a critical component of farmers' tree management, and during the growing season, the stress responses of apple trees induced by various N fertilization can result in unbalanced growth and physiological disorders. Global transcriptome data from previous studies [20,21] and recent studies have suggested examining the different responses to N tolerance in apple tissues [22,23]. However, little is known about the underlying molecular mechanisms of responsive metabolic signals associated with various N stress conditions in apple.…”
Section: Introductionmentioning
confidence: 99%